Exploring anti-cancer activities of epidermal growth factor-immobilized polymeric nanoparticles - Shota Yamamoto; Chia-Jung Chang; Masao Kamimura; Jun Nakanishi (Science and Technology of Advanced Materials)
Cytotoxic agents targeting the epidermal growth factor receptor (EGFR) exhibit significant potential for cancer therapy as EGFR is overexpressed in various cancers. As alternatives to conventional EGFR inhibitors (EGFRi), which exert side effects on non-cancer cells, EGF-immobilized gold nanoparticles exhibit selective cytotoxicity in EGFR-overexpressing cancer cells by locally enhancing EGFR activation and modulating signal transduction through a signal condensation mechanism. However, considering real therapeutic applications, it is important to confirm that the same principle can be applied to polymeric nanoparticles, which are more suitable carriers owing to their biodegradability and biocompatibility, remains unclear. Therefore, in this study, we aimed to investigate the anti-cancer activities of EGF-conjugates with two kinds of polymeric nanoparticles: polystyrene nanoparticles and polymeric micelles. Initial mechanistic studies on phosphorylation signaling and cholesterol depletion revealed that EGF-polystyrene nanoparticles exhibited cytotoxicity against human cervical adenocarcinoma HeLa cells via local enhancement of EGFR activity in membrane rafts. Moreover, EGF-polymeric micelles exerted selective anti-cancer effects against EGFRi-resistant MDA-MB468 refractory triple-negative breast cancer cells after optimization of particle size. These results suggest that the unique anti-cancer effects of EGF nanoparticles are not dependent on the carrier platform. Furthermore, EGF nanoparticles exhibited high cytotoxicity against cancer cells responding poorly to conventional EGFR-targeted anti-cancer drugs, showing potential for future medical applications.